Breast milk fatty acid composition of women living far from the coastal area in Brazil - Renata Y. Nishimura; Gabriela S.F. de Castro; Alceu A. Jordão Junior; Daniela S. Sartorelli (Elsevier, 2013)
Objectives: To evaluate the fatty acid composition of mature human milk of women living far from the coastal area of Brazil. Methods: Mature breast milk samples were obtained from 47 lactating women aged between 18 and 35 years, who delivered their babies at term and who exclusively or predominantly breastfed. Milk collection took place after the fifth week postpartum by hand expression. The fatty acid composition of the milk was determined by gas chromatography. Results: It was observed that the concentration of eicosapentaenoic acid (0.08%) was higher than that observed in previous studies in Brazil. However, the content of docosahexaenoic acid (0.09%) found in human milk was one of the lowest verified in the world. The content of trans fatty acids (2.05%) was similar to that reported in national studies previous to the mandatory declaration of this fatty acid content in food labels, suggesting that this measure had no effect on reducing the content of this fatty acid in the usual diet of women. Conclusions: Low levels of docosahexaenoic acid and high concentrations of trans fatty acids were observed in mature breast milk of women living far from the coastal area in Brazil. Resumo: Objetivos: Avaliar a composição de ácidos graxos do leite humano maduro de mulheres residentes em área distante da costa litorânea brasileira. Métodos: Amostras de leite materno maduro foram obtidas de 47 mulheres lactantes com idade entre 18 e 35 anos, que tiveram partos a termo e em aleitamento exclusivo ou predominante. A coleta de leite se deu a partir da 5ª semana pós-parto, por meio de ordenha manual. A composição de ácidos graxos do leite foi determinada por cromatografia gasosa. Resultados: Verificou-se que a concentração de eicosapentaenoico (0,08%) foi superior ao observado em estudos brasileiros prévios. Entretanto, o teor de docosa-hexaenoico (0,09%) encontrado no leite humano foi um dos menores já verificados no mundo. O teor de ácidos graxos trans (2,05%) foi similar ao relatado em estudos nacionais prévios à obrigatoriedade de declaração do teor deste em rótulos de alimentos, sugerindo que esta medida não surtiu efeito na redução de seu teor na dieta habitual das mulheres. Keywords: Fatty acids, Human breast milk, Lactation, Palavras-chave: Ácidos graxos, Leite materno, Lactação